Pterygium: degeneration, exuberant wound healing or benign neoplasm? - Tradjutrisno, Nurbuanto (Faculty of Medicine, Trisakti University, 2009)
Pterygium is a condition characterized by the encroachment of a fleshy triangle of conjunctival tissue into the cornea. Despite various studies, the pathogenesis of pterygium remains unclear. Chronic exposure to sun is the only factor of which the role has been clearly documented by epidemiologic and in vitro studies. Recent studies have provided data such as loss of heterozygosity and microsatellite instability, decreased apoptosis, increased growth factors, increased p53 expression, telomerase activity, and presence of oncogenic viruses, which support the concept that pterygia can be considered a neoplastic condition. Some of results are contradictory and some features were only found in a proportion of pterygia; this may be due to differences in methodology and study population, but may also be indicative of multiple causative factors. This implies that the pterygium should be viewed as a final common outcome of various etiological factors, such as geography and ethnicity, with ultraviolet radiation-induced damage as the main factor. Thus the pterygium remains an enigma, having the features of an exuberant growth but also those of a benign neoplasm. In this connection there is a need for a unifying theory capable of explaining all of the characteristics of the pterygium.